SENSITIVITY OF SALIVARY GLANDS TO RADIATION- AN OVERVIEW - Vijaya Kumaran, Ghayathri; Jagannathan, Nithya (International Journal of Psychosocial Rehabilitation, 2020)
Radiation therapy for head and neck cancer causes significant secondary side effects in normal salivary glands, resulting in diminished quality of life for these individuals. Salivary glands are exquisitely sensitive to radiation and display acute and chronic responses to radiotherapy and the side effects, including xerostomia, dysphagia, and malnutrition, which are linked to significant reductions in patients’ quality of life. This review will discuss clinical implications of radio sensitivity in normal salivary glands, compare animal models used to investigate radiation-induced salivary gland damage, address therapeutic advances, and project future directions in the field.